Technology Integration in Learning to Read the Al-Qur'an - Tri Bimantoro, Rizal; Alias, Muhamad Firdaus Bin; Syafrianto, Hendra; Abdi, Hamdani; Rahmi, Elvi; K, Munawir (Institute of Research and Community Service STAI Yayasan Tarbiyah Islamiyah Kota Padang, 2024)
This paper explains “Digital Literacy For The Better Generation (DALIBIN): Learning Assistance for the Qur'an and Literacy Empowerment in the Pati District towards Achieving Sustainable Development Goals (SDGs)